Supported ionic liquid-like phases as efficient solid ionic solvents for the immobilisation of alcohol dehydrogenases towards the development of stereoselective bioreductions. Issue 15 (13th July 2021) - Porcar, Raul; Lavandera, Iván; Lozano, Pedro; Altava, Belen; Luis, Santiago V.; Gotor-Fernández, Vicente; García-Verdugo, Eduardo
Abstract : Supported ionic liquids have been evaluated for the immobilisation of the alcohol dehydrogenase from Rhodococcus ruber (ADH-A). The resulting biocatalytic systems remain active after consecutive uses, prolonged storage and under flow conditions. Abstract : Polymeric materials containing ionic liquid fragments, like those found in bulk ILs, are excellent solid media for the immobilisation of biocatalysts. Herein, the entrapment of the enzymatic system formed by alcohol dehydrogenase from Rhodococcus ruber (ADH-A) overexpressed in E. coli and its coenzyme has been studied. The activity, stability and reusability of these preparations have been investigated in the bioreduction of prochiral ketones finding excellent levels of conversion and selectivity. Interestingly, the immobilised enzyme remained active and exhibited excellent stability in aqueous solutions after several recycling uses. More importantly, these biopolymer materials retained most of their activity after consecutive reaction cycles, prolonged storage and under flow conditions.